Renal vascular disease - Textor, Stephen C.; Lerman, Lilach O. (Springer London, 2014)
This book describes the recent advances in the understanding of the development and management of renal vascular disease (RVD). Current perspectives regarding the epidemiology of atherosclerotic RVD, its clinical manifestations, and the interaction with injury pathways related to the kidney have evolved considerably, and the widespread introduction of non-invasive methods for identification of RVD using ultrasound, CT, and MR imaging has allowed more facile identification of these diseases than ever before. Renal Vascular Disease provides an accessible, up-to-date summary of the pathophysiology and management of RVD. The clinical paradigms that are emerging in the field, both in regards to RVD and its role in chronic kidney disease (CKD), cardiovascular risk, and the cardiorenal syndromes are discussed in this comprehensive text, making it an essential resource for clinicians and investigators who tackle the challenges of RVD.